Women Political Movements After 20 Years of Reformasi in Indonesia - Aditya Perdana; Delia Wildianti (Yayasan Jurnal Perempuan, 2019)
The main question in this article is how is the achievement of women political movements after 20 years of reformation in Indonesia? This article elaborates two things which are foundation reasons for examining why women movement in politics have stagnant position and offering strategic agenda that could be discussed for attracting young women in political arena. There are three main reasons to see women movement after Reformation 1998. First aspect is considering civil society characteristics and also party politics in Indonesia which are unique. Second issue is there are established political interaction between both organizations. Third issue are concerning on electoral competition that is important to highlight. That is how to endorse the winning of women candidates in each election could be achieved. We believe that to build connectivity and linkage between young women generation and party politics is strategic step for party politics for resolving the necessity of women candidacy and their winning opportunities in elections.